A risk framework for using systems approaches to manage horticultural biosecurity risks for market access. (March 2020) - van Klinken, Rieks D.; Fiedler, Kathryn; Kingham, Lloyd; Collins, Kerry; Barbour, Darryl
Abstract: Phytosanitary 'Systems Approaches" comprise two or more independent, phytosanitary measures to reduce the risk of pest and pathogen movement through trade. They are increasingly being used to access markets for fresh fruit and vegetables. However, an overarching risk framework for assessing them is lacking. In this paper we first present an easily implementable risk framework for assessing systems approaches, and then test it through a retrospective analysis of publicly-available, systems-based protocols. Our risk framework is a matrix combining four risk reduction objectives with three production stages (pre-harvest, from harvest to phytosanitary certification and post-certification). The four risk reduction objectives, which explicitly focus on how measures reduce risk rather than how they are implemented, are: i) minimising exposure to pests when fruit are vulnerable; ii) minimising host vulnerability; iii) reducing infestation rate; and iv) reducing establishment likelihood. Of the 60 protocols sourced for our retrospective analysis, 52% targeted multiple pests (arthropods and pathogens) and 66% included fruit flies. The 327 measures included in those protocols (averaging 5.0 per protocol) were mapped against the risk framework, and were further categorised within each risk reduction objective according to how they reduce risk. Measures relating to administration or compliance, or ones considered as standard features in phytosanitary protocols, were excluded from analyses. All but two protocols had measures that addressed multiple combinations of risk reduction objectives and production stages. Most protocols (88%) combined measures that minimise pre-harvest exposure to the pest and measures that reduce infestation rates between harvest and certification. Protocols targeting fruit flies were similar to other protocols in terms of which measures were included and how they were combined. One important limitation of our study was that the publicly-available documents we reviewed mostly focussed on implementation of protocols, and rarely explained how the measures contributed to risk reduction, either individually or in combination. Addressing this gap is a priority. Our risk framework for systems approaches provides a versatile basis for developing and assessing new and more innovative protocols, and can thereby help facilitate safer, and more open, trade of fresh produce. Highlights: Trade in fresh produce is dependent on assurance that product is pest free. We present a risk framework for assessing systems approaches that support trade. The framework combines risk reduction objectives with production stage. Application of the framework to 63 existing protocols provided new insights.